Assessing the determinants of interest rate spread of commercial banks in Kenya: An empirical investigation - Maureen Were; Joseph Wambua (Kenya Bankers Association (KBA), 2013)
Despite the liberalization of the financial sector, high interest rate spreads is still an issue of concern in a number of African countries, including Kenya. This paper investigates the determinants of interest rate spreads in Kenya's banking sector based on panel data analysis. The empirical results show that bank-specific factors play a significant role in the determination of interest rate spreads. These include bank size based on bank assets, credit risk as measured by non-performing loans to total loans ratio, liquidity risk, return on average assets and operating costs. The impact of macroeconomic factors such as real economic growth and inflation is not significant. Similarly, the impact of policy rate as an indicator of monetary policy is found to be positive but weak. On average, big banks have higher spreads compared to small banks. There is need for explore policy options meant to enhance competition in the industry and measures to break market dominance will be one such option. Further, the banking sector needs to explore internal as well as industry-driven strategies that counter some of the bank-specific factors associated with higher spreads. These could range from diversification of products to investment in cost-saving and efficient forms of technology.
Keywords: 330